NUEVAS SINONIMIAS DE TAQUINIDOS CHILENOS - Cortés P., Raúl (Acta Entomológica Chilena, 2022)
lielioprosopa finita Reinhard, 1964, is nolhing elsc than an anomalous male of Spanipalpus anstralis Townsend, 1928, wilhout ocellar bristles, while Eithelioprosopa pactilis Reinhard, 1964, is again an anomalous male of Chiloepalpns aurens (Aldrich), 1926 & 1934 with ocellar bristles and discals in the intermedíate segments of the abdomen, this latler condition already mentioned by Dr. Aldrich (1934) as alypical in the gcnus. Both species come from Central Chile and the types are depositcd at the California Academy of Sciences, San Francisco, California, where they were cxamincd by the author May 1974.